Percepção de riscos ambientais de populações vulneráveis a inundações e deslizamentos de dunas em Natal-RN - Cavalcante, Juliana da Silva Ibiapina (2013)
In urban, flooding and landslides are among the troubles that most bring human and material loss. Therefore, this study objected to perform an analysis on the risk perception on the population living in social environmental vulnerable places in order to understand what is the way this population realize the risks they are exposed to and what are the outbrave strategies the develop. The first analyzed area was Complexo Passo da Pátria for the flooding risk problematic and then the Cidade Nova neighborhood threatened by the dunes slides. The areas locate, respectively, in the West and East zones of Natal-RN. Using an interview screenplay adapted from risk perception researches from different brazilian cities, it was collected primarily data on the variables: perception, evaluation and choice, safety threshold, adjustment, decision and participation. Due to the studied areas characteristics the qualitative approach adjusted itself to the difficulties for accessing the areas. The studied places characterize for its insecure situation like selling/using drugs, robbery and murder among others. Due to this situation the interviewed individuals were the ones that could be found more accessibly and available in the moment and the interviews were made in the community leader presence of each area. Through the discourse of the respondents analysis it was able to conclude that the interviewed population is exposed to a high vulnerability grade and risks. However it was identified substantial differences between the perception and risks of Complexo Passo da Pátria and bairro Cidade Nova, because in the first area the intervied ones can recognize the high risk they are exposed to in a more emphatic way to the interviewed ones for the Cidade Nova neighborhood. Furthermore, there is a heavy dissatisfaction for the population of the two places about the city hall positions relating to the present problems in the studied areas. It was also identified the strategy development of acquaintanceship with the risk in the research places beyond a feeling of belonging and affection between the dwellers and the places, yet it was more evident for Complexo Passo da Pátria. Though this analysis it was possible to understand and perceptions and the behavior of the individuals or social groups facing the risks as acceptance and rejection of determined risks beyond adaptation measures of living together with the persistence presence of risks. Therefore, qualitative nature researches emphasizing the perception approach are in the fundamental importance in the studies about risks making it possible to offer aids to the urban planning and management in the implement of effective preventive measures and compatible with the population aims